RESPECT OF THE NATIONAL IDENTITY IN THE LAW OF THE EUROPEAN UNION: POTENTIAL FOR INTERPRETATION AND CASE–LAW OF THE EUROPEAN COURT OF JUSTICE - Jarašiūnas, Egidijus (Teisė, 2015)
Article 4 (2) of the Treaty of the European Union, in its version following the adoption of the Lisbon Treaty, proclaims that the European Union shall respect the national identities of its Member States, inherent in their political and constitutional fundamental structures, inclusive of regional and local self-government. This clause can be compared with the third paragraph of the preamble of the Lithuanian Constitutional Act of Membership of Lithuania in the European Union, which states that the Union shall respect national identity and constitutional traditions of its Member States. One can note that the clause on the respect by the European Union of the national identities of its Member States is the result of a desire to ensure a balance between the strengthening of the European integration process and the protection of the national identities of Member States.Legal doctrine recognises the clause of respect, by the European Union, of the national identities of its Member States as a legal principle. According to the doctrine, this principle is important not only for the EU legal system, but also for the interaction between the EU and its Member States’ legal systems. Authors analyse the diverse aspects of this principle (cultural, political- institutional) and the relationships between national and constitutional identities. Legal doctrine has proposed a wide range of possible meanings of this principle, which can be used as a basis for a serious reflection on the potential judicial interpretation and application of this principle.The European Court of Justice, which is the official interpreter of EU law, applies the clause of respect for national identities of EU Member States in its case-law together with other legal elements (such as fundamental rights, proportionality, protection of public order etc.) on which it grounds its decisions. The judgments of the Court of Justice in Omega, Spain v United Kingdom, Sayn-Wittgenstein, and Runevič-Vardyn and Wardyn cases are examples of this principle being used in European case-law. This principle is usually applied in the case-law of the European Court of Justice in order to draw limits of fundamental freedoms and principles of EU law in individual cases.Because of the impact of the principle of respect for national identities of Member States on the balance between the European and the national legal systems, a dialogue between the ECJ and the national constitutional courts for the convergence of their positions is necessary.